Foot and ankle strength, range of motion, posture and deformity are associated with balance and functional ability in older adults - Spink, M.; Fotoohabadi, M.; Wee, E.; Hill, Keith; Lord, S.; Menz, H. (WB Saunders, 2011)
Objective: To determine the extent to which measures of foot and ankle strength, range of motion, posture, and deformity are associated with performance in a battery of balance and functional ability tests in older adults. Design: Cross-sectional study of people over 65 years. Setting: Community. Participants: Participants (N=305; age range, 65–93y) recruited for a randomized trial investigating the efficacy of a podiatry intervention to prevent falls. Interventions: Not applicable. Main Outcome Measures: Clinical measures of foot and ankle strength (using hand-held dynamometry), range of motion, posture, and deformity, and a battery of balance tests (postural sway, maximum balance range, lateral stability, coordinated stability) and functional ability tests (alternate step test, sit-to-stand, timed 6-m walk). Results: Most (67/88) of the correlations between the foot and ankle tests and performance on the balance and functional tests were statistically significant. Hierarchic linear regression analysis identified hallux plantar flexion strength and ankle inversion-eversion range of motion to be the most consistent significant and independent predictors of balance and functional test performance, explaining up to 25% of the variance in the test scores. Conclusions: Foot and ankle characteristics, particularly plantar flexor strength of the hallux and ankle inversion-eversion range of motion, are important determinants of balance and functional ability in older people. Further research is required to establish whether intervention programs that include strengthening and stretching exercises for the foot and ankle may achieve improvements in balance and functional ability and reduce the risk of falls in older people.